Funções Reais através da integração Complexa - Silva, Aico Alves de Oliveira (Universidade Federal do Tocantins, 2020)
Integrals are an important mathematical tool with many applications, and of relevant interest to who know them, and especially to who use them. Thus, this paper presents alternative methods for problem solving with real function integrals. Specifically, for solving these integrals through the complex integration, we will present methods that seek, if not facilitate, at least show that there are other ways to solve these types of problems. For this, several references from different authors were used, reaching the expected conclusions. Also, we will present several examples of real functions being integrated by complex methods, and relying mainly on the residual theorem. Finally, we apply these studied methods as a problem solving tool in the Probability area.